The HDL handbook : biological functions and clinical implications - Komoda, Tsugikazu (Elsevier Ltd. : Academic Press, 2017)
The HDL Handbook: Biological Functions and Clinical Implications, Third Edition, brings laboratory research in HDL from bench to bedside in a reference format for both researchers and clinicians studying cholesterol, lipids, epidemiology, biochemistry, molecular medicine, and pathophysiology of cardiovascular diseases. Information presented is valuable for the development of clinical trials with the aim of improvement of HDL-C levels and the prevention of cardiovascular events. Highlights of this new edition include the science underpinning HDL metabolism including information on HDL-C metabolism, gene expression, gene-bioactive compounds interaction, and post-translational modifications of gene expression of apo-lipoproteins.